First Record of Dina Lineata (Hirudinea: Erpobdellidae) in Greater Zab River Kurdistan Region-Iraq - ALI, LUAY A.; JAWAIR, HAYFA J. (Science Journal of University of Zakho, 2013)
The leech Dina lineata (Müller, 1774) was recorded in the present study for the first time in Iraq, from samples collected on the stone from Greater Zab River west of Erbil city during a period from May to September 2006. The body was rounded with red coloration and although they move by extending and contracting its body.